Acute Responses to Forearm Compression of Blood Lactate Accumulation, Heart Rate, Perceived Exertion, and Muscle Pain in Elite Climbers - Engel, Florian Azad; Sperlich, Billy; Stöcker, Urs; Wolf, Peter; Schöffl, Volker; Donath, Lars (Frontiers in Physiology, 2018)
Objectives: To evaluate the immediate responses to forearm compression of blood lactate concentration, heart rate, perceived exertion and local forearm muscle pain during severe climbing in elite climbers. Method: Seven elite climbers (18 ± 2 yrs; 164 ± 5 cm; 57.8 ± 5.3 kg) performed 3 × 3 climbing bouts with maximal intensity on a distinct 8 m boulder wall (lead grade: 7a–8b) in a single blinded, placebo-controlled cross-over design, wearing either forearm sleeves with compression (verum-compression) or placebo forearm sleeves with no compression (falsum-compression). Each climber’s heart rate was recorded during and capillary blood lactate concentration, perceived exertion and forearm muscle pain were assessed directly after climbing. Result: Heart rate (p=0.45, ηp²=0.12), blood lactate concentrations (p=0.44, ηp²=0.10), perceived exertion levels (p=0.51, ηp²=0.08) and pain perception (p=0.67, ηp²=0.03) were not affected by forearm compression. No condition × time interaction effect (compression × time) occurred for heart rate (p=0.66, ηp²=0.04), blood lactate concentration (p=0.70, ηp²=0.02), perceived exertion (p=0.20, ηp²=0.26) and pain perception (p=0.62, ηp²=0.04). Conclusion: In elite climbers performing severe climbing bouts, sleeves with forearm compression do not alter blood lactate concentration, heart rate, perceived exertion and local forearm muscle pain.